The Philippines' voluntary national review on the sustainable development goals - Reyes, Celia M.,Albert, Jose Ramon G.,Tabuga, Aubrey D.,Arboneda, Arkin A.,Vizmanos, Jana Flor V.,Cabaero, Carlos C. (Philippine Institute for Development Studies, 2019)
United Nations member-states, including the Philippines, committed to the 2030 Agenda for Sustainable Development and the Sustainable Development Goals (SDGs) to
10419/211084
Keywords: Graue Literatur; Sustainable Development Goals; Voluntary National Review; quality education; decent work and economic growth; reduced inequalities; climate action; peace; justice and strong institutions; partnerships